Cable Vector Collision Detection Algorithm for Multi-Robot Collaborative Towing System - Li, Tao; Zhao, Zhigang; Zhu, Mingtong; Zhao, Xiangtang (Shanghai jiao tong da xue xue bao, 2025)
For the process of multi-robot collaboration to lift the same lifted object by flexible cables, the existing collision detection algorithm of cables between the environmental obstacles has the problem of misjudgment and omission. In this work, the collision detection of cable vector was studied, and the purpose of collision detection was realized by algorithm. Considering the characteristics of cables themselves, based on oriented bounding box theory, the cable optimization model and environmental obstacle model were established, and a new basic geometric collision detection model was proposed. Then a fast cable vector collision detection algorithm and an optimization principle were proposed. Finally, the rationality of the cable collision detection model and the effectiveness of the proposed algorithm were verified by simulation. Simulation results show that the proposed method can meet the requirements of the fast detection and the accuracy in complex virtual environment. The results lay a foundation for obstacle avoidance motion planning of system.